Analyzing determinants of social practices in infectious diseases among Indigenous and Afro-Colombian communities: A participatory diagnosis of malaria, tuberculosis, and leishmaniasis in Colombia. - Martha Milena Bautista Gomez; Laura Sofia Zuluaga; Marcos Medina Tabares (PLOS Global Public Health)
Infectious diseases pose major public health challenges worldwide, particularly in developing countries, where their impact is more severe. This article presents a participatory social diagnosis to analyze the determinants of health-related social practices associated with infectious diseases (malaria, tuberculosis, and leishmaniasis) among Indigenous and Afro-Colombian communities in Pueblo Rico, Colombia. We explore how social determinants, attitudes, and knowledge influence health-related practices. Our findings show that each disease is shaped by a different dominant factor: malaria by structural conditions, leishmaniasis by attitudes, and tuberculosis by limited knowledge, while all are affected by distrust in the health system and low awareness of self-care. We argue that health practices are complex, historically structured social practices, so their change requires a long-term holistic health approach. Through this research, we seek to understand health practices related to infectious diseases and to inform the design of more effective and culturally grounded interventions.